Contextual theology: skills and practices of liberating faith - Bergmann, Sigurd; Vähäkangas, Mika (Routledge new critical thinking in religion, theology and biblical studies, 2021)
"This book advances that history by exploring stories, images and discourses across a worldwide range of geographical, cultural and confessional contexts. Its twelve authors not only enrich our understanding of the significance of the contextual method, but also produce a new range of original ways of doing theology in contemporary situations. The authors discuss some prioritised thematic perspectives with an emphasis on liberating paths, and expand the ongoing discussion on the methodology of theology into new areas. Themes such as interreligious plurality, global capitalism, ecumenical liberation theology, eco-anxiety and the anthropocene, postcolonialism, gender, neo-pentecostalism, world theology, and reconciliation are examined in situated depth. Additionally, voices from Indigenous lands, Latin America, Asia, Africa, Australia, and Europe and North America enter into a dialogue on what it means to contextualise theology in an increasingly globalised and ever-changing world. Such a comprehensive discussion of new ways of thinking about and doing contextual theology will be of great use to scholars in Theology, Religious Studies, Cultural Studies, Political Science, Gender Studies, Environmental Humanities, and Global Studies"--